Home care in the unified health system: reflection about the organization process and management (Research, Society and Development, 2020)
The research objective was analyze how the organization and management of Home Care of the Unified Health System represented by the Better at Home Program and to reflect on about the opportunities and challenges of this program in care production. Theoretical and reflective study based on literature and critical analysis of the authors. The home care is demanded by assistance actions of full character and extended that go from health promotion to rehabilitation. The Better at Home Program has as potential to allow a integral care at home. As a challenge highlighted the articulation with health services that integrate the Health Care Network. The management of the home care in Brazil has presented a substantial advancement of expansion and qualification the offer services at home. It is urgent the consolidation of the home care as a form of substitute attention and potential to produce new forms of health care.